THE ROLE OF LEADERSHIP EMPOWERMENT ON EMPLOYEE ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AT PT X WITH PROACTIVE BEHAVIOR AS A MEDIATOR VARIABLE - Riyanthi, Farah Almas; Matulessy, Dr. Andik; Rini, Dr. Rr. Amanda Pasca (Srawung: Journal of Social Sciences and Humanities, 2024)
Positive leadership empowerment may encourage positive attitudes in employee organizational citizenship behavior. This behavior could be enhanced by the proactive behavior of the employees. This research aims to determine the role between leadership empowerment on employee organizational citizenship behavior at PT X with proactive behavior as a mediator variable. The implementation of this research is in the production department of PT X on full-time employees with a total of 270 subjects with random sampling techniques. The instrument used is a questionnaire. For proactive behavior variables, the authors developed it based on Crant's theory. Organizational Citizenship Behavior (OCB) variables were measured using the OCB Scale developed by Organ. Meanwhile, the leadership empowerment variable was measured using the Empowering Leadership Questionnaire (ELQ) developed in previous research by Arnold, Arad, Rhodes, and Drasgow. Research data analysis using linear regression statistical techniques and path analysis. The results of the research data analysis explain that there is a significant influence of leadership empowerment on employee organizational citizenship behavior at PT X with proactive behavior as a mediator variable (p = 0.046, p < 0.05), where proactive behavior partially mediates organizational citizenship behavior.